Distributed localization using normalized quad lateration in LoRa networks: application for tourist position estimation - Musayyanah Musayyanah; Prima Kristalina; Yosefine Triwidyastuti; Pauladie Susanto; Mochammad Zen Samsono Hadi (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
The tourism sector has been growing rapidly along with the decline of COVID-19. This sector should pay attention to safety and security, which is by tracking the position of tourists. In this work, we propose a tourist positioning tracking system. A node containing a microcontroller with LoRa wireless communication called unknown node (UN) is assembled as a wearable device. We use the received signal strength indicator (RSSI)-based localization technique with an additional normalization method to correct the error rate in position estimation. This method estimates the distance between the anchor node (AN) and UN to approximate the actual distance value. Three-dimensional position tracking (longitude, latitude, altitude) of five UN surrounded by four AN was performed using the quadlateration method. The estimation process was carried out by the UN whereas receiving information is transmitted from the four AN. The communication between AN and UN used a scheduling algorithm on all AN. The position estimation error of the five UNs was measured using mean square error (MSE) yields 20.73 m, 50.32 m, 32.92 m, 21.40 m, and 16.89 m respectively. The accuracy of the estimated distance obtained by the proposed normalization quadlateration method is increased up to 15.22%.